2015
DOI: 10.21608/taec.2015.12145
|View full text |Cite
|
Sign up to set email alerts
|

An annotated checklist of Egyptian mosses

Abstract: The presented list of Egyptian mosses includes 181 taxa in 56 genera, 17 families and 10 orders. Synonyms reported only from Egypt are given in a separate list. The distribution of the 181 mosses in the 11, hitherto, surveyed phytogeographic territories of Egypt shows that S, Mm, Cai and Di are the richest territories regarding the number of recorded taxa. Pottiaceae, Bryaceae and Funariaceae dominate the flora. Pohlia lescuriana (Sull.) Ochi is a new record to Egypt. Other relevant annotations are also given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…From the political and administrative perspective, Eurasia includes Europe and Asia (excl. the Sinai Peninsula, which is usually linked to Africa; being part of Egypt, though geographically it is located in Asia; anyhow Plagiothecium had never been reported from Sinai, see [ 225 ]). The area covered by the present checklist includes 107 countries of Europe and Asia, some well-separated islands, and archipelagos.…”
Section: Methodsmentioning
confidence: 99%
“…From the political and administrative perspective, Eurasia includes Europe and Asia (excl. the Sinai Peninsula, which is usually linked to Africa; being part of Egypt, though geographically it is located in Asia; anyhow Plagiothecium had never been reported from Sinai, see [ 225 ]). The area covered by the present checklist includes 107 countries of Europe and Asia, some well-separated islands, and archipelagos.…”
Section: Methodsmentioning
confidence: 99%
“…Number of moss taxa now from Egypt has been quietly increased in the last decade into 188 taxa belonging to 59 genera, 17 families and 10 orders (El-Saadawi et al, 2013 a,b;Ibrahim et al, 2013;Hassan et al, 2017;El-Sakaty et al, 2018;Khalil and Farag, 2018;Taha, 2020). The distribution of the 188 moss taxa in the 11 surveyed phytogeographical territories of Egypt (out of 13 territories) showed that Southern Sinai, Western Mediterranean Costal Land, Cairo, and Isthmic Desert of Egypt are the richest territories regarding the number of recorded moss taxa (El-Saadawi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Egyptian moss flora currently includes 186 taxa belonging to 59 genera, 17 families and 10 orders (El-Saadawi et al, 2015;Khalil & Farag, 2018). Thirty two taxa are now known from the Oases of the Western Desert belonging to 14 genera, 6 families and 4 orders.…”
Section: Introductionmentioning
confidence: 99%
“…In Egypt, Bryaceae includes 28 taxa representing 15% of the Egyptian moss flora (El-Saadawi et al, 2015). In the oasis, Bryaceae includes 15 taxa representing about 47% of the total moss flora (followed by Pottiaceae 11 taxa).…”
Section: Introductionmentioning
confidence: 99%